Evaluation of the cone-beam computed tomography accuracy in measuring soft tissue thickness in different areas of the jaws - Ehsan Moudi; Sina Haghanifar; Maryam Johari; Hemmat Gholinia; Mohammad Kazemi Ghanbarabadi (Wolters Kluwer Medknow Publications, 2019)
Purpose: Due to the extensive use of cone-beam computed tomography (CBCT) in dentistry, especially in measuring thicknesses of hard and soft tissues, and the fact that CBCT has low contrast resolution, the aim of this study was to evaluate the accuracy of CBCT in measuring soft tissue thickness. Materials and Methods: In this cross-sectional study, pink baseplate wax as a soft tissue simulation was overlaid in different areas of the jaws on the dry human skull, and the probe was used to determine the thicknesses of 1, 2, 3, and 5 mm. These thicknesses were then measured accurately with a digital caliper by one person four times at interval of a week. The skull was scanned using two CBCT scanners, and the different thicknesses of wax were measured by two observers four times with a week interval. The CBCT measurements were compared with digital caliper measurements as a reference. Results: Statistical analysis showed no significant difference between CBCT and digital caliper measurements for thickness < 2 mm (P > 0.05). Conclusions: Statistically, the difference between digital caliper and CBCT measurements was < 0.1 mm, but this difference is not clinically important. The accuracy of CBCT in measuring soft tissue thickness was 0.1 mm.